Factors Influencing Mobile Banking Service Quality and Its Relationship with Customer Satisfaction and Loyalty at Bank Mandiri - Adithya Ipung Wicaksana; Asma’I Ishak (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the factors influencing mobile banking service quality and their relationship with customer satisfaction and loyalty at Bank Mandiri. The research focuses on five dimensions of service quality: assurance, reliability, security, responsiveness, and usability. Data was collected through an online survey distributed to 315 respondents, all users of the Livin’ by Mandiri application, aged between 17–50 years. The study employed Structural Equation Modeling (SEM) using AMOS 26 to test the proposed hypotheses. The findings reveal that service quality significantly influences customer satisfaction but does not have a direct effect on customer loyalty. Additionally, factors such as assurance, reliability, security, responsiveness, and usability were found to have varying impacts on service quality. This study highlights the need for Bank Mandiri to enhance its mobile banking features to strengthen customer satisfaction and loyalty. Further research is suggested to expand the scope of the study to other banking institutions.